Bioceramic micro-fillers reinforce antibiofilm and remineralization properties of clear aligner attachment materials - Jiang, Wenhui; Wang, Zhejun; Zhou, Yinghong; Shen, Ya; Yen, Edwin; Zou, Bingshuang (Frontiers in Bioengineering and Biotechnology, 2024)
Clear aligners, while offering a more hygienic alternative to fixed appliances, are still associated with challenges including plaque accumulation and enamel demineralization. The aim of the present study was to investigate the antibiofilm and remineralization effectiveness of innovative flowable composite attachments containing bioceramic micro-fillers. Four experimental attachments were formulated and bonded to human enamel specimens: 3M Filtek Supreme flowable composite (Filtek SF) + 10% bioactive glass 45S5 (BAG), Filtek SF + 30% BAG, Filtek SF + 10% Bredigite (BRT), Filtek SF + 30% BRT. Plaque biofilms were grown on the bonded enamel using a standardized protocol and the biofilmkilling effect was assessed by confocal laser scanning microscopy and viability staining. Attachments with bioceramic fillers significantly inhibited plaque biofilm growth in 3 weeks on enamel, contributing over 20% bacterial cell killing in 10% filler groups and over 30% killing in 30% filler groups. Vickers microhardness was measured to evaluate the remineralization effect of the attachments containing bioceramic fillers after acid challenge. All four experimental groups demonstrated significantly higher microhardness values than the control group without fillers on the attachment side.The shear bonding strength was not compromised in the attachments with micro-fillers. Proper incorporation of bioceramic micro-fillers in attachments provides an innovative approach for clear aligner therapy with reinforced antibiofilm and remineralization effects without weakening shear bonding strength.